Can lifestyle preferences help explain the persistent gender gap in academia?: the “mothers work less” hypothesis supported for German but not for U.S. early career researchers - Sieverding, Monika; Neubauer, Andreas B. (PLOS ONE, 2018)
Do lifestyle preferences contribute to the remaining gender gap in higher positions in academia with highly qualified women—especially those with children—deliberately working fewer hours than men do? We tested the “mothers work less” hypothesis in two samples of early career researchers employed at universities in Germany (N = 202) and in the US (N = 197). Early career researchers in the US worked on average 6.3 hours more per week than researchers in Germany. In Germany, female early career researchers with children had drastically reduced work hours (around 8 hours per week) compared to male researchers with children and compared to female researchers without children, whereas we found no such effect for U.S. researchers. In addition, we asked how long respondents would ideally want to work (ideal work hours), and results revealed similar effects for ideal work hours. Results support the “mothers work less” hypothesis for German but not for U.S. early career researchers.